Releasing the Lockerbie Bomber: National Interests, Intergovernmental Relations and Para-Diplomacy. Issue 4 (November 2017) - Kenealy, Daniel
Abstract : In his recent book The Lockerbie Bombing: The Search for Justice, Kenny MacAskill recounts his decision to release Abdelbaset Al-Megrahi, the only man convicted of the Lockerbie bombing. Eight years have passed since Al-Megrahi's release on compassionate grounds. In the book MacAskill ranges far beyond the events in which he was closely involved, recounting the bombing itself, the subsequent investigation, trial and appeals in an effort to offer a comprehensive account of the Lockerbie bombing. In this article I review the book and return to some of the key issues raised by MacAskill's decision and the broader context in which it was made. I argue that the book sheds little new light on Lockerbie and that it falls short in precisely the areas where MacAskill might have the most insight to offer. It is a rather bloodless and legalistic account that renders the complexities and the shades of grey of international politics in black and white. The case will nevertheless remain fascinating to scholars of intergovernmental relations in the UK, of para-diplomacy, and of international politics.